Global Peatland Carbon Pool Sizes: Current Estimates, Uncertainties, and Future Research Directions - Yongxing Ren; Dehua Mao; Hanxiang Liu; Jianbao Liu; Zicheng Yu; Mohamed Abdalla; Xiuxue Chen; Heyu Chen; Zongming Wang; Pete Smith (Global Change Biology, 2026)
Because peatlands store vast amounts of carbon and are highly sensitive to climate warming, an accurate estimation of the size of their global carbon pools is essential for understanding the terrestrial carbon cycle and future climate feedback. Yet current estimates remain highly uncertain due to inconsistent definitions, different estimation methods, incomplete field sampling, and limited information on peatland extent and depth. Here we synthesize recent advances in peatland carbon accounting, including peatland definitions, carbon sink function, and carbon pool components. We compile estimates globally, and for northern and tropical peatlands, and evaluate the main drivers of uncertainty across methods. Current estimates of global peatland extent range from ~3.8 to 4.9 × 10 6 km 2 , and corresponding carbon pool estimates span 238–612 Gt C, reflecting a two‐ to three‐fold spread. Although intact peatlands continue to sequester ~0.1–0.3 Gt C year −1 , degraded peatlands emit ~1.9 Gt CO 2 ‐eq year −1 (~4% of anthropogenic greenhouse gas emissions), highlighting their dual role as both a carbon sink and a rapidly mobilizable carbon source. We show that peatland area and peat depth are the dominant sources of global uncertainty, while bulk density and soil organic carbon content become critical at regional scales. We propose a pathway toward reducing this uncertainty, based on harmonized peatland definitions, improved depth mapping, and integration of remote sensing, process‐based models, and machine learning. These advances are essential for producing policy‐relevant, climate‐relevant peatland carbon assessments.